Case report: Major pathologic response induced by neoadjuvant treatment using BRAF and MEK inhibitors in a patient with stage IIIA lung adenocarcinoma harboring BRAF V600E-mutation - Liu, Chaoyuan; Lu, Min; Yang, Yang; Wang, Xiang; Ma, Fang; Liu, Xianling (Frontiers in Oncology, 2022)
Targeted therapy has achieved great success in advanced non-small lung cancer (NSCLC) with driver genes, and neoadjuvant-targeted therapy is increasingly being investigated. Although neoadjuvant-targeted therapy with EGFR-TKI and ALK-TKI showed good efficacy, there is no report of neoadjuvant-targeted therapy to BRAF V600E mutation on NSCLC so far. Here, we report the first case of a successful neoadjuvant-targeted therapy with BRAF and MEK inhibitors followed by radical surgical excision with major pathologic response (MPR) in a patient with stage IIIA lung adenocarcinoma (LUAD) harboring BRAF V600E mutation. The case informs us that targeted therapy with BRAF and MEK inhibitors could be administrated as a neoadjuvant strategy for selected cases of NSCLC harboring BRAF V600E mutation.